DRDO E-Journal Consortium in Defence Science and Technology - Senthil, V; Madhusudhan, M (DESIDOC Journal of Library & Information Technology, 2018)
Defence Research and Development Organisation (DRDO) E-Journal Consortium is one of the important consortiums among other consortia existing in India. It covers multi-disciplinary subject areas to fulfill the information needs of DRDO scientific community. This paper tries to evaluate the implementation of DRDO e-journals, coverage of publishers and titles, subject-wise distribution of titles among DRDO laboratories, need of e-journal consortium among the labs, and expenditure details along with yearly growth. This is one of the unique consortiums implemented that is based on subscription model.The study also highlights the usage of e- journals publisher-wise in the consortium and would be helpful in efficient collection development policy of e-journals.